2023
DOI: 10.3389/fpsyt.2023.1150422
|View full text |Cite
|
Sign up to set email alerts
|

Mentalizing and epistemic trust as critical success factors in psychosomatic rehabilitation: results of a single center longitudinal observational study

Abstract: BackgroundInpatient psychosomatic rehabilitation is a key treatment for patients with mental health issues. However, knowledge about critical success factors for beneficial treatment outcomes is scarce. The aim of this study was to evaluate the association of mentalizing and epistemic trust with the improvement of psychological distress during rehabilitation.MethodsIn this naturalistic longitudinal observational study, patients completed routine assessments of psychological distress (BSI), health-related quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…As these invariances corroborated the suitability of the ETMCQ for meaningful cross-sex contrasts, we compared mean scores, revealing that females scored higher on ET and lower on EM. This finding is partially congruent with Campbell et al (2021), who found similar patterns for ET and EM but also significant differences for EC; partially congruent with and Riedl, Rothmund et al (2023), who found similar patterns but only for ET; and inconsistent with Liotti, Milesi et al (2023), who found no cross-gender differences for the subscales.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…As these invariances corroborated the suitability of the ETMCQ for meaningful cross-sex contrasts, we compared mean scores, revealing that females scored higher on ET and lower on EM. This finding is partially congruent with Campbell et al (2021), who found similar patterns for ET and EM but also significant differences for EC; partially congruent with and Riedl, Rothmund et al (2023), who found similar patterns but only for ET; and inconsistent with Liotti, Milesi et al (2023), who found no cross-gender differences for the subscales.…”
supporting
confidence: 60%
“…We aimed to evaluate the psychometric properties of the ETMCQ employment status; Campbell et al, 2021;Liotti, Milesi, et al, 2023;Riedl, Rothmund, et al, 2023;Tanzer et al, 2021).…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It involves a tendency for epistemic naivety, which results in a higher liability to misinformation and a risk of exploitation (Campbell et al, 2021). Studies have shown that these three dimensions (trust, mistrust, and credulity) are distinct in both nonclinical and clinical samples (Kampling et al, 2022;Riedl et al, 2023). For example, individuals with borderline personality disorder have been shown to have high levels of both epistemic mistrust and epistemic credulity (Orme et al, 2019).…”
Section: Epistemic Trust Mentalizing and Severity Of Depressionmentioning
confidence: 99%
“…University students must continuously evaluate the credibility of information from various sources to make informed decisions and succeed academically. Building epistemic trust enables students to engage critically with academic materials, seek guidance from fellow students and mentors and participate actively in classroom discussions (Campbell et al, 2021;Kampling et al, 2022;Riedl et al, 2023). A welldeveloped sense of epistemic trust is a prerequisite for a supportive learning environment, encouraging knowledge sharing and cooperative learning.…”
Section: Introductionmentioning
confidence: 99%